(untitled) (Comprehensive Journal of Science, 2025)
This exploratory study intended to explore the third year secondary school students’ perceptions about the role of technology-enhanced social media in developing English language learning. It adopted an adapted questionnaire to collect data from students in order to see how social media can affect various aspects of language skills, such as, students’ language skill improvement, motivation, confidence, and their learning attitudes. The participants included 55 students from two secondary schools in Tripoli. The findings of the study showed that secondary school students generally viewed social media platforms as an important learning resource for language learning which improved their vocabulary, communication, pronunciation, and listening skills. The findings of the study also indicated that the role of these social media platforms increased students’ motivation and reduced their anxiety level when using social media for learning. However, students perceived the role of social media in improving their grammar and error correction as limited and weak. Furthermore, although many students preferred learning trough social media over traditional learning methods, enjoyment levels varied considerably, indicating various learners’ preferences. The study concluded that social media can serve as an additional learning tool that supports independent learning but should be incorporated within formal classroom instruction for language development. Finally, this study recommended that EFL education should involve adopting blended learning approaches and provide guided social media activities to maximize its learning outcomes.